1989
DOI: 10.1002/j.1556-6676.1989.tb02493.x
|View full text |Cite
|
Sign up to set email alerts
|

Career Counseling and Life Planning With Lesbian Women

Abstract: The psychological development and "coming out" process of lesbian women are examined with regard to career planning. The interaction of these issues with a model of lesbian identity provides a framework for career counselors who work with individuals or lesbian couples. F reud contended that the basic requirements of human existence are love and work. For women who are blending a lesbian life-style and a career, there are particular considerations that need to be examined before these requirements can be met. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 16 publications
4
34
0
2
Order By: Relevance
“…(2011, p. 259). From bluecollar craft jobs and commercial truck driving to army mechanics and gymnastic teachers (for lesbians), and professional dancers and church organists to sailors and interior designers (for gay men), many scholars have noted the strikingly high concentration of lesbian and gay workers in certain occupations (Badgett, 1995;Bailey & Oberschneider, 1997;Bérubé, 2011;Hetherington & Orzek, 1989;Whitam, 1986). One of the first studies to report national estimates of gay and lesbian occupational concentration used U.S. Census data for same-sex partners in 33 of the largest professions and showed that gay men and lesbians were "concentrated in the [professional] fields that focus on creativity, psychology/counseling, and law/social work" (Baumle et al, 2009, p. 168).…”
Section: What Makes Sexual Minority Workers Distinct From Other Workers?mentioning
confidence: 99%
“…(2011, p. 259). From bluecollar craft jobs and commercial truck driving to army mechanics and gymnastic teachers (for lesbians), and professional dancers and church organists to sailors and interior designers (for gay men), many scholars have noted the strikingly high concentration of lesbian and gay workers in certain occupations (Badgett, 1995;Bailey & Oberschneider, 1997;Bérubé, 2011;Hetherington & Orzek, 1989;Whitam, 1986). One of the first studies to report national estimates of gay and lesbian occupational concentration used U.S. Census data for same-sex partners in 33 of the largest professions and showed that gay men and lesbians were "concentrated in the [professional] fields that focus on creativity, psychology/counseling, and law/social work" (Baumle et al, 2009, p. 168).…”
Section: What Makes Sexual Minority Workers Distinct From Other Workers?mentioning
confidence: 99%
“…These nontraditional roles, combined with the expectation of being self-supporting through their lives, provide the motivation for lesbians to pursue male-dominated careers, which will likely be higher paying than traditionally woman-dominated careers (Chung, 1995). Lesbians' double minority status contributes to the complexities that they confront in life and career planning (Hetherington and Orzek, 1989). Lesbians often realize early in life that they will not marry, so they tend to invest more heavily in preparing for careers than straight women do (Black, Makar, Sanders, and Taylor, 2003).…”
Section: Lesbian Identitymentioning
confidence: 99%
“…In research conducted with heterosexual, gay, and lesbian college students, lesbians showed the least amount of uncertainty about their career decision making (Hetherington and Orzek, 1989), and lesbians and heterosexual men were the most satisfied with their career choices. An awareness of the need to support themselves, as well as the frequent devaluation of traditionally female jobs in the lesbian community (Morgan and Brown, 1991), may further encourage lesbians to consider nontraditional, and usually more highly paid, careers (Fassinger, 1995).…”
Section: Advantages Of Being a Lesbian In The Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…To avoid bias, some gay men and lesbians prefer to sort into occupations that they perceive as more "gay-friendly" (Chung, 1995). Because of limited self-awareness, constriction of self-concept, and lower social support, gay men and lesbians may prematurely foreclose on career choices (Hetherington & Orzek, 1989;Prince, 1995), possibly leading to suboptimal choice of field of education and career. Moreover, in adolescence, the primary context for validation, self-esteem, and autonomy involves acceptance by a peer group.…”
Section: H1mentioning
confidence: 99%